2017
DOI: 10.1093/ejcts/ezx016
|View full text |Cite
|
Sign up to set email alerts
|

The value of fluorine-18 deoxyglucose positron emission tomography scans in patients with ventricular assist device specific infections†

Abstract: PET-CT scan findings showed a high specificity and positive predictive value for VAD-specific infections. Therefore, it may have the potential to guide the clinician in handling patients with infectious complications after VAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In other studies, observers were either not blinded to clinical context of patients or assessment of non-attenuation-corrected images was not described. Two studies performed the reference test fully in accordance with ISHLT recommendations [27,29]. Two studies had high applicability concerns for both index test and reference test, because they focused on the LVAD driveline only [19,20].…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, observers were either not blinded to clinical context of patients or assessment of non-attenuation-corrected images was not described. Two studies performed the reference test fully in accordance with ISHLT recommendations [27,29]. Two studies had high applicability concerns for both index test and reference test, because they focused on the LVAD driveline only [19,20].…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…In all studies, FDG-PET scans were performed on a hybrid PET/CT system, combining an FDG-PET scan with a lowdose CT for anatomical reference and attenuation correction. In one study, the FDG-PET scan was combined with diagnostic CTA [27]. Reporting of injected activity differed between studies: while some reported an injected activity per kilogram of body weight, others reported a mean total injected activity with lower and upper ranges.…”
Section: Technical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bernhardt et al [29] reported the sensitivity of FDG PET/CT in LVAD infections as 87.5%, the specificity as 100%, the PPV as 100%, and the NPV as 86.7%. They also confirmed the utility of FDG PET/CT in the location and quantification of the extent of infection.…”
Section: Left Ventricular Assist Device Infectionmentioning
confidence: 99%
“…3,[16][17][18] In this issue, de Vaugelade et al 19 retrospectively analyzed the diagnostic performance of both radiolabeled leucocyte scintigraphy and 18F-FDG PET/CT in 24 LVAD-recipients with suspected devicerelated infection. Their conclusion is that 18F-FDG PET/CT demonstrated a higher sensitivity compared to radiolabeled leucocyte scintigraphy and could be preferred as first-line radionuclide imaging procedure.…”
mentioning
confidence: 99%